Toxicity of naproxen sodium and its mixture with tramadol hydrochloride on fish early life stages. (December 2017) - Sehonova, Pavla; Plhalova, Lucie; Blahova, Jana; Doubkova, Veronika; Prokes, Miroslav; Tichy, Frantisek; Fiorino, Emma; Faggio, Caterina; Svobodova, Zdenka
Abstract: Pharmaceuticals occur in water bodies as a consequence of their incomplete removal during waste water treatment processes. The occurence of pharmaceuticals in surface waters as well as their possible impact on aquatic vertebrates have received considerable attention in recent years. However, there is still a lack of informations on the chronic effects of widely used drugs as well as their possible mixture toxicity on non-target aquatic vertebrates as well as their possible mixture toxicity. The aim of this study was to assess the effects of naproxen sodium on early life stages of fish and evaluate its mixture toxicity with tramadol hydrochloride, which was assessed in our earlier study as a single substance. Two embryo-larval toxicity tests with common carp ( Cyprinus carpio ) were performed according to the OECD guideline 210 (Fish, Early-life Stage Toxicity Test) in order to assess the subchronic toxicity of naproxen sodium and tramadol hydrochlorid-naproxen sodium mixture at the concentrations of 10; 50; 100 and 200 μg/L. These experiments were conducted for 32 days. The subchronic exposure to naproxen sodium and naproxen sodium and tramadol hydrochloride mixture had a strong effect on the early life stages of common carp. Hatching, developmental rate, morphology, histopathology and, in the case of the naproxen sodium and tramadol hydrochloride mixture, mortality were influenced. The bioindicators of oxidative stress were also influenced. The LOEC was determined at 10 μg/L for both naproxen sodium and naproxen sodium and tramadol hydrochloride mixture. Highlights: Increased mortality (50%) was observed after exposure to the substance mixture. Developmental disruptures were observed. Higher number of skin mucous cells and gill lamellas' deformations were observed. Tramadol and naproxen mixture exposure revealed in oxidative stress. The lowest observed effect concentration was estimated to be 10 μg/L.